2023
DOI: 10.5551/jat.63789
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Analyses of the Treatment Conditions in Patients Initiating Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) Inhibitor in Taiwan

Abstract: Aims: Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor is a powerful low density lipoprotein cholesterol (LDL-C)-lowering therapy, but this drug is expensive. This study aimed to describe the real-world treatment conditions in patients initiating PCSK9 inhibitor in Taiwan.Methods: This was a multicenter, retrospective, and observational study. The clinical characteristics, baseline lipid-lowering therapy, and changes in the lipid profile of patients receiving PCSK9 inhibitor treatment were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Using real-world data, Lin et al showed a slightly lower LDL-C reduction effect from PCSK9 inhibitors compared with the clinical trial data 5) . One potential reason for the reduced LDL-C lowering effects, the authors highlight, is a pattern of spacing out injection times for each PCSK9 inhibitor due to its high cost.…”
Section: See Article Vol 30: 000-000mentioning
confidence: 99%
See 1 more Smart Citation
“…Using real-world data, Lin et al showed a slightly lower LDL-C reduction effect from PCSK9 inhibitors compared with the clinical trial data 5) . One potential reason for the reduced LDL-C lowering effects, the authors highlight, is a pattern of spacing out injection times for each PCSK9 inhibitor due to its high cost.…”
Section: See Article Vol 30: 000-000mentioning
confidence: 99%
“…Given the current state, driven to some degree by "ability and willingness to pay" for PCSK9 inhibitors, what can we do to more effectively deliver this useful but relatively expensive drug to the right patients? Lin et al concluded in their paper that we need to find ways to tackle the reimbursement restriction together with physicians, governments, insurance systems, and pharmaceutical companies 5) .…”
Section: See Article Vol 30: 000-000mentioning
confidence: 99%